Expression of glycosylated haloalkane dehalogenase LinB in Pichia pastoris - Nakamura, Takashi; Zámocký, Marcel; Zdráhal, Zbynĕk; Chaloupková, Radka; Monincová, Marta; Prokop, Zbynĕk; Nagata, Yuji; Damborský, Jirí (Protein expression and purification, 2006)
Heterologous expression of the bacterial enzyme haloalkane dehalogenase LinB from Sphingomonas paucimobilis UT26 in methylotrophic yeast Pichia pastoris is reported. The haloalkane dehalogenase gene linB was subcloned into the pPICZalphaA vector and integrated into the genome of P. pastoris. The recombinant LinB secreted from the yeast was purified to homogeneity and biochemically characterized. The deglycosylation experiment and mass spectrometry measurements showed that the recombinant LinB expressed in P. pastoris is glycosylated with a 2.8 kDa size of high mannose core. The specific activity of the glycosylated LinB was 15.6 +/- 3.7 micromol/min/mg of protein with 1,2-dibromoethane and 1.86 +/- 0.36 micromol/min/mg of protein with 1-chlorobutane. Activity and solution structure of the protein produced in P. pastoris is comparable with that of recombinant LinB expressed in Escherichia coli. The melting temperature determined by the circular dichroism (41.7+/-0.3 degrees C for LinB expressed in P. pastoris and 41.8 +/- 0.3 degrees C expressed in E. coli) and thermal stability measured by specific activity to 1-chlorobutane were also similar for two enzymes. Our results show that LinB can be extracellularly expressed in eukaryotic cell and glycosylation had no effect on activity, protein fold and thermal stability of LinB.
Keywords: Recombinant Proteins; Enzyme Stability; denaturace proteinů; Cloning, Molecular; Gene Expression Regulation, Enzymologic; klonování DNA; Hydrolases; Sphingomonas; regulace genové exprese u bakterií; hydrolasy; Circular Dichroism; rekombinantní proteiny; stabilita enzymů; kinetika; konformace proteinů; regulace genové exprese enzymů; cirkulární dichroismus; Protein Denaturation; Protein Conformation; glykosylace; Glycosylation; Kinetics; Pichia; Gene Expression Regulation, Bacterial